Quantification of Subdural Electrode Shift Between Initial Implantation, Postimplantation Computed Tomography, and Subsequent Resection Surgery. Issue 1 (January 2019) - Fan, Xiaoyao; Roberts, David W; Kamal, Yasmin; Olson, Jonathan D; Paulsen, Keith D
Abstract : BACKGROUND: : Subdural electrodes are often implanted for localization of epileptic regions. Postoperative computed tomography (CT) is typically acquired to locate electrode positions for planning any subsequent surgical resection. Electrodes are assumed to remain stationary between CT acquisition and resection surgery. OBJECTIVE: : To quantify subdural electrode shift that occurred between the times of implantation (Crani 1), postoperative CT acquisition, and resection surgery (Crani 2). METHODS: : Twenty‐three patients in this case series undergoing subdural electrode implantation were evaluated. Preoperative magnetic resonance and postoperative CT were acquired and coregistered, and electrode positions were extracted from CT. Intraoperative positions of electrodes and the cortical surface were digitized with a coregistered stereovision system. Movement of the exposed cortical surface was also tracked, and change in electrode positions was calculated relative to both the skull and the cortical surface. RESULTS: : In the 23 cases, average shift of electrode positions was 8.0 ± 3.3 mm between Crani 1 and CT, 9.2 ± 3.7 mm between CT and Crani 2, and 6.2 ± 3.0 mm between Crani 1 and Crani 2. The average cortical shift was 4.7 ± 1.4 mm with 2.9 ± 1.0 mm in the lateral direction. The average shift of electrode positions relative to the cortical surface between Crani 1 and Crani 2 was 5.5 ± 3.7 mm. CONCLUSION: : The results show that electrodes shifted laterally not only relative to the skull, but also relative to the cortical surface, thereby displacing the electrodes from their initial placement on the cortex. This has significant clinical implications for resection based upon seizure activity and functional mapping derived from intracranial electrodes.